An Atlas.Ti Analysis of the Collaboration of Human Development Cadres Family Assistance Teams in Stunting Prevention - Putri, Dian Utama Pratiwi; Indriani, Diah; Mahmudiono, Trias (Indonesian Journal of Global Health Research, 2024)
In the implementation of stunting convergence in Pringsewu District in 2023, there is no direct coordination between the Human Development Cadres and the Family Assistance Team and no way to facilitate collaboration between the human development cadres and the family assistance team to work together to carry out data collection tasks as indicators of stunting achievement and stunting prevention in Pringsewu District. Objective to find out more about the phenomenon of human development cadres and family human assistenace teams collaboration and the perspectives of each agency representative in Pringsewu District, Lampung Province that allows human development cadres and family assitance team collaboration to be carried out in stunting prevention efforts in Pringsewu District, Lampung Province. The type of research used was qualitative using a phenomenological approach and data collection techniques with in-depth interviews and FGDs which were analysed using Atlas t.i version 8. The informants in this study were from the relevant Dinas and OPD in the Pringsewu Regional Government work area. Data collection was carried out using in-depth interviews and FGD techniques which were analyzed using Atlas t.i version 8. From the results of the analysis of the synthesis of interviews and Focus Group Discussions with informants from the relevant Departments and OPDs in the Pringsewu Regional Government work area, it was found that the collaboration between human development cadres and family assistance teams was very needed for the effectiveness and efficiency of human development cadres and family assistance team work as stunting cadres. Collaboration between human development cadres and family assitance team should be facilitated by the Pringsewu Regency Team for Accelerating Stunting Reduction and advocated to the Pringsewu Regency Regional Government for inclusion in the PRINCES (Pringsewu Prevent Stunting) Program. Collaboration between Human Development Cadres and Family Assistance Workers is very crucial in efforts to reduce stunting. This collaboration needs to be facilitated by the Stunting Reduction Acceleration Team and integrated into the PRINCES (Pringsewu Prevent Stunting) program.